Care farming, learning and young people: An exploration into the possible contribution of care farming to young people’s engagement with learning - Rachael Fell-Chambers (Educational Futures)
This paper focuses on the qualitative findings from a study that explored the possible contribution of care farming to young people’s engagement with learning. Firstly, the perceptions and experiences of young people accessing alternative curriculum on three care farms were gathered through a methodological approach underpinned by aspects of ethnography. Secondly, care farm providers and school support staff were consulted to provide a deeper understanding into why young people attend care farms, and to ascertain if they felt there were any perceived benefits to their learning.